Study of determination of laboratory turnaround time in tertiary care hospital in India - Wankar, Abhinav Dileep (International Journal of Research in Medical Sciences, 2017)
Turnaround time (TAT) is commonly defined as the time from when a test is ordered until the result is reported. TAT is often considered the most significant measure of a laboratory’s service and is used by many clinicians to judge its quality. Timely reporting of laboratory test results is now considered an important aspect of the services provided by the clinical laboratory. It has also been shown that outcomes in certain situations such as operation theaters and in emergency departments have been affected by timely reporting of lab tests results. Rapid laboratory turnaround times are important both from a medical and commercial point of view. The study was conducted from 1 April 2013 to 31 May 2013. Out of total 232 samples, 183 samples (78.88%) were taken for analysis. 100 (54.65%) samples were within TAT time and 83 (45.35 %) samples were delayed. Out of total 83 samples which were delayed, 48 (57.83%) samples had TAT between 60 minutes to 90 minutes, 22 (26.51%) samples had TAT between 90 minutes to 120 minutes, 9 (10.84%) samples had TAT between 120 minutes to 180 minutes, and 4 (4.82%) samples had TAT over 180 minutes. Average time between sample collection and lab reach was observed to be 15 min. 38 sec. Transport delay was observed. Instrumentation failure was observed in biochemistry - 2 times and thyroid - 1 time. Hence this study aims to evaluate the delay and reason of delay of turnaround time (TAT) of stat tests in section of clinical chemistry of the clinical laboratory.